Incentive to Breastfeeding: Assessment of the Nurse's Role in Primary Health Care (Research, Society and Development, 2022)
Breastfeeding (BF) offers benefits for both the baby and the mother, such as bonding and child development. In this research, a cross-sectional, exploratory and descriptive study was carried out, with a qualitative approach, with the objective of analyzing the guidelines provided as a way of encouraging BF by nurses to pregnant women at the Basic Health Unit (BHU). The study was developed with two nursing professionals and nine pregnant women in a primary care unit in the city of Lajeado - RS. After data collection, the responses were analyzed and thematic categories were constructed. The results reveal that the age of pregnant women ranges from 24 to 41 years and schooling from 8 to 15 years of study. All pregnant women want to breastfeed, but three of them have doubts about BF, such as attachment, mastitis and breast fissures. In addition, six of them reported not having received guidance on BF. But all responded that they know the importance of BF. In relation to the two nurses, the results showed that they have worked at the BHU for 1.5 to 4 years, have specialization and always talk to pregnant women about the importance and advantages of breastfeeding. We conclude that nurses are trained in breastfeeding guidance and that pregnant women are interested in breastfeeding and are aware of the importance of this practice.